(untitled) (INTERNATIONAL SEMINAR, 2024)
This study explores students’ understanding of the concept of Islam Rahmatan Lil ’Alamin in the context of religious moderation. Using qualitative methods, in-depth interviews with five students revealed that (40%) demonstrated a very good understanding, (40%) a good understanding, (20%) a fair understanding, and (0%) a poor understanding. The majority of students apply the values of tolerance, justice, and compassion in their daily lives, although some face obstacles such as limited access to moderate literature (40%), social pressures (50%), and challenges in academic discussions and religious activities (60%). In conclusion, this study recommends that higher education institutions play a more active role in deepening students’ understanding through curriculum enhancement, training, and interfaith dialogue to foster an inclusive and tolerant campus environment.